Social Climber Di Era Milenial Dalam Al-Quran (Studi Penafsiran Q.S Al-Isra’ Ayat 37 Dalam Tafsir Al-Misbah Karya Quraish Shihab) - Ariana; Nasution, Muhammad Roihan; Fitriani (Al-Wasathiyah: Journal of Islamic Studies, 2023)
Ariana, 2022, The number of negative impacts regarding milenial social phenomena is more ofthen this social social climber who has negative or violates islamic law. Because in the Qur’an it is explained that the purpuse of this how the solution to this social climber is to remember Allah, be selective in choosing friend, avoid hedonism, avoid useles meeting so that we avoid social climber behavior. Is a tescrictive qualitative research. This research also uses the library research method or literature study with a data analysis approach in the interpretation methodology that the authour uses in this study the tahlili method. The tahlili approach interprets surah Al-Isra verse 37 regarding social climber in or the prohibition of social climber in the verse. This study shows how this verse prohibit social climber in social media in this is millenial era. In this discussion, there is tafsir Quraish Shihab. According to tafsir Quraish Shihab, social climber is a prohibition on arrogance, because arrogance is the biggest direction in acquiring knowledge that leads to virtue and serious illness that breeds ignorance so that it leads the perpetrators to evil.